2016
DOI: 10.1183/13993003.01778-2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-immune interactions in chemical-induced airway hyperreactivity

Abstract: Asthma may be induced by chemical sensitisers, via mechanisms that are still poorly understood. This type of asthma is characterised by airway hyperreactivity (AHR) and little airway inflammation. Since potent chemical sensitisers, such as toluene-2,4-diisocyanate (TDI), are also sensory irritants, it is suggested that chemical-induced asthma relies on neuro-immune mechanisms.We investigated the involvement of transient receptor potential channels (TRP) A1 and V1, major chemosensors in the airways, and mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 53 publications
3
34
0
1
Order By: Relevance
“…Non-specific airway hyperreactivity to methacholine, lung inflammation and immunologic responses are assessed one day later [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Non-specific airway hyperreactivity to methacholine, lung inflammation and immunologic responses are assessed one day later [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The authors proposed that the AHR following exposure to hypochlorite and ovalbumin depends on a neuroimmune interaction that involves TRPA1-dependent stimulation of sensory neurons and mast cell activation, although the rationale is not obvious given AHR to direct contractile agents is not thought to have a neuronal component as they are thought to activate airway smooth muscle directly [125]. Another article by the same authors demonstrated that TRPA1, TRPV1 and mast cells play an indispensable role in the development of TDI-elicited AHR [126]. In the context of COPD-relevant disease biology, cigarette smoke extract has been shown to evoke IL-8 release from human epithelial cells, smooth muscle cells and fibroblasts and cigarette smoke and acrolein have been shown to release keratinocyte-derived chemokine (murine orthologue) in a murine model.…”
Section: Trpa1mentioning
confidence: 99%
“…FOT measurements have already been used in mouse models of respiratory diseases to investigate pathophysiological changes associated with fibrosis [3], emphysema [4], or asthma [58]. Yet, from a pre-clinical perspective, the translational value of the mouse as a model to study respiratory diseases has been challenged and it is not always clear how changes in respiratory mechanics parameters relate to the commonly measured forced expiration (FE) parameters in humans [9].…”
Section: Introductionmentioning
confidence: 99%